Reaktor Fitoremidiasi sebagai Pengolah Limbah Cair Tekstil di Kampung Batik Jetis, Kelurahan Lemahputro, Kabupaten Sidoarjo : Reaktor Fitoremidiasi sebagai Pengolah Limbah Cair TekstilReaktor Fitoremidiasi sebagai Pengolah Limbah Cair Tekstil - Khilyatul Afkar; Layyinatul Khoiriyah; Miftahul Khoiriyah; Siti Rahayu Primayanti; Mohamad Gofur; Intan Surul Chasanah Putri2; Maschan Yusuf Musthofa; Amallia Lindawati; Aida Nurmala; Andre Septianto; Dwi Putri Rahayu; Listin Fitrianah1; Luqman Hakim (Universitas Nahdlatul Ulama Sidoarjo, 2021)
Batik is one of Indonesia's cultural treasures that is popular and worldwide. However, behind the manufacturing process, batik creates textile liquid waste that requires processing because it contains hazardous substances. Kampung Batik Jetis Sidoarjo is one of the locations for batik craftsmen in Indonesia. Textile liquid waste contains a lot of hazardous substances such as dyes, heavy metals, and suspended solids. On average, textile wastewater in Indonesia contains 750 mg/l suspended solids and 500 mg/l BOD. Comparison of COD:BOD is in the range of 1.5:1 to 3:1. Phytoremediation is an environmentally friendly method that is widely used to treat waste. Water hyacinth is a phytoremediator plant used in this activity because it has the ability to absorb pollutants that are cheap and easy to find. Phytoremediation reactor is used to assist the process of Phytoremediation. This activity aims to educate the people of Kampung Batik Jetis in processing textile liquid waste and being able to build a phytoremediation reactor. The benefits obtained are that the hazardous substances in textile wastewater are reduced and are safely disposed of in water bodies. The results obtained in this activity are increasing the knowledge of the people of Kampung Jetis in processing textile liquid waste using a Phytoremediation reactor.